(untitled) (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2014)
Ultra cold atomic condensate with long range interaction is considered as a possible candidate to realize the supersolid phase. Such a supersolid phase can be subjected to artificial gauge field created either through rotation or by introducing space dependent coupling among hyperfine states of the atoms using Raman lasers. We study the effect of an artificial gauge field on the Supersolid phase in ultracold atomic condensates with long range interactions. Using Mean field approach, we demonstrate the structural differences between vortex in a supersolid and superfluid. We determine analytically the effect of the artificial gauge field on the density wave - supersolid (DW-SS) and the Mott insulator-superfluid (MI-SF) transition boundary. We also point out that in symmetric gauge the momentum distribution structure at these transition boundaries bears distinctive signatures of vortices in supersolid and superfluid phases. We point out that these results can clearly identify such a ultra cold atomic supersolid phase.